Insulin Promotes the Proliferation of Human Umbilical Cord Matrix-Derived Mesenchymal Stem Cells by Activating the Akt-Cyclin D1 Axis. (18th April 2017) - Li, Peng; Wei, Jinsong; Gao, Xiang; Wei, Bo; Lin, Hao; Huang, Rui; Niu, Yanru; Lim, Kyu; Jing, Kaipeng; Chu, Jiaqi
Abstract : Background . The functions of insulin in mesenchymal stem cells (MSC) remain poorly understood. Methods. MSC from human umbilical cord matrix (UCM) cultured in serum-free media (SFM) with or without insulin were subjected to various molecular biological analyses to determine their proliferation and growth states, expression levels of Akt-cyclin D1 signaling molecules, and in vitro differentiation capacities. Results. Insulin accelerated the G1-S cell cycle progression of UCM-MSC and significantly stimulated their proliferation and growth in SFM. The pro-proliferative action of insulin was associated with augmented cyclin D1 and phosphorylated Akt expression levels. Akt inactivation remarkably abrogated insulin-induced increases in cyclin D1 expression and cell proliferation, indicating that insulin enhances the proliferation of UCM-MSC via acceleration of the G1-S transition mediated by the Akt-cyclin D1 pathway. Additionally, the UCM-MSC propagated in SFM supplemented with insulin exhibited similar specific surface antigen profiles and differentiation capacities as those generated in conventional media containing fetal bovine serum. Conclusions. These findings suggest that insulin acts solely to promote UCM-MSC proliferation without affecting their immunophenotype and differentiation potentials and thus have important implications for utilizing insulin to expand clinical-grade MSC in vitro.